2013
DOI: 10.22401/jnus.16.3.24
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Electrical Behavior of Polymer Matrix Composite and their Hybrids Reinforced with (Carbon Black–Boron) Particles

Abstract: The work is designed to study experimentally the mechanical and electrical behavior of polymer matrix composites and their hybrids which reinforced by carbon black particles with constant volume fraction (10)% and boron particles with different volume fractions (0,2,4,and 6)% which are bounded with unsaturated polyester resin. Number of mechanical tests were done, they include (hardness, Charpy impact,and bending strength), which done at room temperature in Iraq .Results of the work show that the values of har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Results showed increasing in hardness values with volume fractions of boron powder. It is observed the values of hardness are increased with increasing volume fraction of reinforced boron particles to matrix due to the boron particles have excellent hardness compared with black carbon particles, in hybrid composite material: polyester resin reinforced with hybrid particles of (black carbon-boron), the hardness increase with contain of boron [4]. Saleh et al studied mechanical properties of epoxy filled with fly ash and silica fume added each filler separately with various ratios as (10%, 20%, 30%, 40%, 50%), their results showed that the increase of additives ratios of silica fume and fly ash caused increasing the compression strength and tensile strength, the increase of additives ratio of silica fume causes decreasing in bending strength [5].…”
Section: Flores Et Al Studied the Influence Of Filler Structure Onto ...mentioning
confidence: 96%
“…Results showed increasing in hardness values with volume fractions of boron powder. It is observed the values of hardness are increased with increasing volume fraction of reinforced boron particles to matrix due to the boron particles have excellent hardness compared with black carbon particles, in hybrid composite material: polyester resin reinforced with hybrid particles of (black carbon-boron), the hardness increase with contain of boron [4]. Saleh et al studied mechanical properties of epoxy filled with fly ash and silica fume added each filler separately with various ratios as (10%, 20%, 30%, 40%, 50%), their results showed that the increase of additives ratios of silica fume and fly ash caused increasing the compression strength and tensile strength, the increase of additives ratio of silica fume causes decreasing in bending strength [5].…”
Section: Flores Et Al Studied the Influence Of Filler Structure Onto ...mentioning
confidence: 96%